ANALYSIS OF THE BADE WHEELED PHENOMENON IN THE NGABEN CEREMONY STRUCTURE IN BALI - Arya Pageh Wibawa (Bajang Institute, 2022)
The purpose of the analysis of the Bade Wheeled Phenomenon in the Ngaben Ceremony Structure in Bali is to reveal the meaning of Wheeled Bade. Bade is known in traditional Balinese culture as an important tool in the Ngaben Ceremony in Bali. However, some Balinese people have replaced the word